Transition and coherence in intellectual property law essays in honour of Annette Kur - Bruun, Niklas 1950-; Dinwoodie, Graeme B. 1966-; Levin, Marianne 1942-; Ohly, Ansgar 1965- (Cambridge intellectual property and information law, 2020)
The nature and content of intellectual property (IP) law, which is heavily contingent on the state of technology and on social and market developments, has always been subject to ongoing transitions. How those transitions are effected and the shape they take is crucial to the ability of IP to achieve its stated goals and provide the necessary climate for investment in creativity, innovation and brand differentiation. Yet the need for change can run headlong into a desire for coherence. A search for coherence tests the limits of the concept of "intellectual property," is imperiled by overlaps between different IP regimes, and calls for a unifying normative theme. This volume assembles contributors from across IP and the globe to explore these questions, including whether coherence is desirable. It should be read by anyone interested in understanding the conceptual underpinnings of one of the most important and dynamic areas of the law